FACTORS THAT AFFECT TAXPAYER COMPLIANCE IN KPP PRATAMA GAMBIR 4 2018 - Akbar, Fhatur; Nuryatno, Muhammad (Jurnal Reviu Akuntansi dan Keuangan)
Tax is one of the main resources in the implementation of activities such as taxes that are taxed will be difficult to do from the tax sector.Â This study aims to find out and know the duties of taxes, taxes required, taxes, and tax avoidance on taxes. This data uses primary data as data obtained from data used in the Gambir Empat Primary KPP environment. The sample used was 125 respondents registered at the KPP Pratama Jakarta Gambir Empat. Data collection using purposive sampling method and analyzed using the SPSS version 24 application.The results of this study show the results in general and the variables of of positive taxpayers. Therefore, all the hypotheses in this study can be accepted.